Monitoreo sequias agricolas en la región central oriental de la provincia de La Pampa (Argentina) - Vergara, Gabriela; Casagrande, Guillermo; Fuentes, Maria Elena; Belmonte, María Laura; Mendez, Mariano; Arnaiz, Juan Pablo (Asociación Argentina de Agrometeorología, 2023)
EEA Anguil